2020
DOI: 10.1038/s41598-020-73192-z
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-dependent circuits anchored in the dorsal and ventral left anterior insula

Abstract: The hub role of the right anterior insula (AI) has been emphasized in cognitive neurosciences and been demonstrated to be frequency-dependently organized. However, the functional organization of left AI (LAI) has not been systematically investigated. Here we used 100 unrelated datasets from the Human Connectome Project to study the frequency-dependent organization of LAI along slow 6 to slow 1 bands. The broadband functional connectivity of LAI was similar to previous findings. In slow 6-slow 3 bands, both dor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 85 publications
(142 reference statements)
3
13
0
Order By: Relevance
“…Actually, a previous study reported that the major frequency contributions to resting-state FC resulted from fluctuations <0.1 Hz (Cordes et al, 2001). Furthermore, RSNs have also been observed in the 0.1-0.2 Hz band (Wu et al, 2008;Salvador et al, 2008;Baria et al, 2011;Niazy et al, 2011;Gohel and Biswal, 2015;Wang et al, 2018Wang et al, , 2020. These previous findings are consistent with our results.…”
Section: Relations Between Dms and Rsnssupporting
confidence: 93%
See 1 more Smart Citation
“…Actually, a previous study reported that the major frequency contributions to resting-state FC resulted from fluctuations <0.1 Hz (Cordes et al, 2001). Furthermore, RSNs have also been observed in the 0.1-0.2 Hz band (Wu et al, 2008;Salvador et al, 2008;Baria et al, 2011;Niazy et al, 2011;Gohel and Biswal, 2015;Wang et al, 2018Wang et al, , 2020. These previous findings are consistent with our results.…”
Section: Relations Between Dms and Rsnssupporting
confidence: 93%
“…These previous findings are consistent with our results. However, other previous studies found RSNs in frequency bands of >0.2 Hz (Lee et al, 2013; Boubela et al, 2013; Gohel and Biswal, 2015; Wang et al, 2020). The inconsistency between the previous results and our results may imply that it is difficult to extract DMs that have a spatial structure similar to those of RSNs in the high-frequency range.…”
Section: Discussionmentioning
confidence: 58%
“…The previous studies have demonstrated that chronic pain patients showed increased high-frequency BOLD oscillations (0.12-0.20 Hz) in the medial prefrontal cortex and parts of default mode network (Baliki et al, 2011). Recently, frequency-dependent bilateral anterior insular networks were identified (Wang et al, 2018b(Wang et al, , 2020c. In our study, decreased FcHo and functional connectivities of default mode network in the frequency band of 0.01-0.1 Hz were found suggesting that the functional abnormalities of the default mode network are present in both low and high frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we also found abnormal FcHo and functional connectivities in sensorimotor and salience networks in the frequency band of 0.01-0.1 Hz. Given the frequency-dependent functional circuits of salience network (Wang et al, 2018b(Wang et al, , 2020c, whether the differences in the two networks are frequency-specific needs to be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our ndings indeed revealed that frontal and insular disconnections play a crucial role in the emergence of DSO. The role of the insula in the sense of body ownership is well known 10,22,27 , interpreted either as contributing to the integration of interoceptive sensations with other signals about the body 10 , or as regulating the salience of sensory signals 9,40 , including during belief updating about sensory states 41 and self-awareness 33 . Indeed, the insula is also part of the salient network, a large-scale brain network identi ed in resting state fMRI studies and connectivity analyses and thought also to relate to the ventral attention network (VAN 42 ), involving the temporoparietal junction and the ventral frontal cortex, connected by the ventral branch of the SLF.…”
Section: Discussionmentioning
confidence: 99%